2014
DOI: 10.1136/bmjqs-2013-002436
|View full text |Cite
|
Sign up to set email alerts
|

We need to talk: an observational study of the impact of electronic medical record implementation on hospital communication

Abstract: The implementation of EMR was associated with a decrease in face-to-face communication between physicians and nurses, and worsened overall agreement about the plan of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 11 publications
1
42
0
Order By: Relevance
“…For example, the implementation of an electronic medical record in a hospital setting has been shown to decrease face-to-face communication between physicians and nurses and worsen overall agreement about the plan of care (Taylor, Ledford, Palmer, & Abel, 2014); in addition, the use of short text messages in GIM has been linked to fewer verbal conversations and face to face interactions (Wu et al, 2014). Reflexivity about organizational routines such as rounds, referral practices and face-to-face and electronic communication can facilitate formal and informal interprofessional negotiations that contribute to high quality patient discharge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the implementation of an electronic medical record in a hospital setting has been shown to decrease face-to-face communication between physicians and nurses and worsen overall agreement about the plan of care (Taylor, Ledford, Palmer, & Abel, 2014); in addition, the use of short text messages in GIM has been linked to fewer verbal conversations and face to face interactions (Wu et al, 2014). Reflexivity about organizational routines such as rounds, referral practices and face-to-face and electronic communication can facilitate formal and informal interprofessional negotiations that contribute to high quality patient discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Receiving multiple instant messages in their busy day may overwhelm the clinicians with information. In fact, a recent study reported that electronic communication worsened the healthcare providers' agreement regarding the plan of care [58].…”
Section: Informatics-based Recommendationsmentioning
confidence: 99%
“…Receiving multiple instant messages in their busy day may overwhelm the clinicians with information. In fact, a recent study reported that electronic communication worsened the healthcare providers' agreement regarding the plan of care [58].Raising awareness on the importance of the information related to fall risk management through educational seminars and training is essential for all HHA clinicians and staff members. Such training can allow clinicians to understand each other's roles and what information each discipline requires to better manage the risk of falls.…”
mentioning
confidence: 99%
“…Also, while it has been demonstrated that the introduction of electronic health records results in changes to the frequency of verbal communication and shared awareness between physicians and nurses [17,18], to our knowledge, no study analyzing the in situ content and characteristics in the era of widespread EHR use has been completed.…”
Section: Introductionmentioning
confidence: 99%